A new look at osteoarthritis: Threshold potentials and an analogy to hypocalcemia - Van Gelder, P.; Audenaert, E.; Calders, P.; Leybaert, L. (Frontiers in Aging, 2023)
Cartilage is a tissue that consist of very few cells embedded in a highly negatively charged extracellular matrix (ECM). This tissue is dealing with several electrical potentials which have been shown to control the production of ECM. Cartilage is present at joints and is constantly prone to degradation. Failing to repair the damage will result in the occurrence of osteoarthritis (OA). This perspective aims to link biophysical insights with biomolecular research in order to provide an alternative view on the possible causes of OA. Firstly, we hypothesize the existence of a threshold potential, which should be reached in order to initiate repair but if not met, unrepaired damage will evolve to OA. Measurements of the magnitude of this threshold electrical potential would be a helpful diagnostic tool. Secondly, since electrical potential alterations can induce chondrocytes to synthesize ECM, a cellular sensor must be present. We here propose an analogy to the hypocalcemia ‘unshielding’ situation to comprehend electrical potential generation and explore possible sensing mechanisms translating the electrical message into cellular responses. A better understanding of the cellular voltage sensors and down-stream signalling mechanisms may lead to the development of novel treatments for cartilage regeneration.